2019
DOI: 10.1055/s-0039-1678733
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Continuous Glucose Monitoring in Gestational Diabetes: A Randomized Controlled Trial

Abstract: Objective To evaluate whether real-time continuous glucose monitoring improves glycemic control over intermittent self-monitoring of blood glucose in gestational diabetes. Study Design We performed a single-institution randomized controlled trial. Patients with gestational diabetes were randomized to use either real-time or blinded continuous glucose monitoring. The primary outcome was mean sensor glucose level during the fourth week of continuous glucose monitoring use. Secondary outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 19 publications
0
40
0
1
Order By: Relevance
“…Paramasivam et al [ 34 ] (MQ) found a significant difference in favor of the intervention group (mean 5.2%, SD 0.4% vs mean 5.6%, SD 0.6%; P =.006). Alfadhli et al [ 33 ] ( P =.168) (MQ) and Lane et al [ 36 ] ( P =.3) (SQ) found lower mean HbA 1c values in their intervention groups ( P >.05).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Paramasivam et al [ 34 ] (MQ) found a significant difference in favor of the intervention group (mean 5.2%, SD 0.4% vs mean 5.6%, SD 0.6%; P =.006). Alfadhli et al [ 33 ] ( P =.168) (MQ) and Lane et al [ 36 ] ( P =.3) (SQ) found lower mean HbA 1c values in their intervention groups ( P >.05).…”
Section: Resultsmentioning
confidence: 98%
“…We identified 4 randomized controlled trials (IG: n=147, CG: n=154). Whereas 3 studies used self-monitoring blood glucose as control [ 33 - 35 ], 1 study used blinded continuous glucose monitoring system which did not display the glucose readings to the participant [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations